Morphometric variation and production constraints of Criollo sheep in the high Andes of southern Peru - Estrada Cañari, Richard (2025)
This study aimed to characterize the morphometric traits and production systems of Criollo sheep in the highlands of Caylloma, Arequipa, Peru. A total of 455 sheep were evaluated using a stratified proportional sampling method across the districts of Tisco, San Antonio de Chuca, and Yanque. Morphometric data were collected under standardized conditions, and nine zoometric indices were calculated to assess functional conformation and productive aptitude. Additionally, 52 sheep producers were surveyed to contextualize herd management practices. Results revealed low levels of formal education and limited technical assistance among producers. Sheep farming was primarily sustained by family tradition, with declining flock sizes attributed to pasture scarcity and climatic challenges. Campaign-based sales strategies and rudimentary reproductive management were prevalent. Health practices showed widespread deworming but limited preventive care. Multivariate analysis indicated significant morphometric variation linked to sex, biotype, and dental stage. This integrative approach highlights both the adaptive potential and production constraints of Criollo sheep in high-altitude environments, providing a basis for developing breeding strategies based on morphometric indices.